BANKING SECTOR EFFICIENCY: A DEA AND TIME SERIES APPROACH - Suflan, Fadzlan (Ekonomika, 2010)
The paper provides a new approach to modeling bank efficiency. Unlike previous bank efficiency studies, the present paper employs the data envelopment analysis (DEA) method on quarterly data to construct the efficiency frontiers. The Malaysian banking sector is used for a case study. The results show that the Malaysian banking sector has exhibited the mean technical efficiency of 97.3%, suggesting the minimal input waste of 2.7%. The empirical findings suggest that the pure technical efficiency outweighs the scale efficiency in determining the Malaysian banking sector’s technical efficiency. The results imply that, although the Malaysian banking sector has been efficient in managerial terms, it has been operating at a non-optimal scale of operations.p>